1995
DOI: 10.1093/hmg/4.11.2047
|View full text |Cite
|
Sign up to set email alerts
|

Detailed mapping and loss of heterozygosity analysis suggests a suppressor locus involved in sporadic breast cancer within a distal region of chromosome band 17p13.3

Abstract: The chromosome region 17p13.3 is thought to encode a tumour suppressor gene involved in sporadic breast cancer and other malignancies. Physical ordering of markers has been carried out by a series of multicolour fluorescent in situ hybridisation (FISH) experiments, using isolated yeast artificial chromosomes (YACs) and cosmids. Eight polymorphic markers ordered within this new physical map and one external marker were used to investigate the pattern of loss of heterozygosity in a panel of 40 sporadic breast tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
57
0

Year Published

1996
1996
2001
2001

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(60 citation statements)
references
References 0 publications
3
57
0
Order By: Relevance
“…British Journal of Cancer (1998) 77(5) YNZ22 allelic imbalance reported in this study (52%) lies within the range (37-65%) previously published by other groups (Chen et al, 1991;Singh et al, 1993;Thorlacius et al, 1993;Comelis et al, 1994;Harada et al, 1994;Ito et al, 1995;Stack et al, 1995). The proportion of cancers with p53 mutation (20%), p53 allele loss (41%), p53 mRNA expression (54%) and overexpression (28%) or p53 protein expression (32%) are similar to the reported series (Cattoretti et al, 1988;Davidoff, 1991;Iwaya, 1991;Kovach et al, 1991;Osborne et al, 1991;Runnebaum et al, 1991;Varley et al, 1991;Vojtesek et al, 1992;Andersen et al, 1993;Barnes, 1993;Friedrichs, 1993;Martinazzi, 1993;Thorlacius et al, 1993;Tsuda et al, 1993;Marks et al, 1994;Bergh et al, 1995;Borressen et al, 1995;Stenmark-Askmalm et al, 1995).…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…British Journal of Cancer (1998) 77(5) YNZ22 allelic imbalance reported in this study (52%) lies within the range (37-65%) previously published by other groups (Chen et al, 1991;Singh et al, 1993;Thorlacius et al, 1993;Comelis et al, 1994;Harada et al, 1994;Ito et al, 1995;Stack et al, 1995). The proportion of cancers with p53 mutation (20%), p53 allele loss (41%), p53 mRNA expression (54%) and overexpression (28%) or p53 protein expression (32%) are similar to the reported series (Cattoretti et al, 1988;Davidoff, 1991;Iwaya, 1991;Kovach et al, 1991;Osborne et al, 1991;Runnebaum et al, 1991;Varley et al, 1991;Vojtesek et al, 1992;Andersen et al, 1993;Barnes, 1993;Friedrichs, 1993;Martinazzi, 1993;Thorlacius et al, 1993;Tsuda et al, 1993;Marks et al, 1994;Bergh et al, 1995;Borressen et al, 1995;Stenmark-Askmalm et al, 1995).…”
Section: Discussionsupporting
confidence: 86%
“…Given that YNZ allele imbalance is more common than p53 mutation in breast cancer, the independence of YNZ22 allele imbalance from any p53 changes suggests that the greater discriminatory power of the YNZ22 locus as a marker for disease behaviour is not simply due to chance. Emerging mapping data for 17pl3.3 (Stack et al, 1995;White et al, 1996) have suggested two regions: YNZ22 and a more telomeric region (defined by markers D17S926, D17S695, D17S849) may be of interest in human breast cancer. Alongside the HIC-1 (hypermethylated in cancer), ABR and CRK genes (Heisterkamp et al, 1989;Morris et al, 1995;Wales et al, 1995) in this region, 17pl3.3 may carry a gene or genes of both scientific interest and clinical importance in breast cancer.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, LOH studies in breast cancer have suggested the presence of another tumoursuppressor gene mapped to chromosomal region 17pl3.3 (Coles et al, 1990;Cornelis et al, 1994;Merlo et al, 1994). Our recent work revealed a complex pattern of LOH in this region in breast tumours (Stack et al, 1995). The highest loss (60-70%), and therefore perhaps the most likely site of the putative suppressor gene, was defined by the three most distal 17p markers, D17S926, D17S695 and D17S849, which were mapped and ordered by fluorescence in situ hybridisation (FISH) to a position near the telomere (for physical map of markers, see Stack et al, 1995).…”
mentioning
confidence: 57%